Learning strategies for english vocabulary in high school students - Arequipa Tandalla, Yesenia Anabel (2016)
Vocabulary is an essential part in the teaching learning process of the English language. Its importance resides in the fact that without enough knowledge of vocabulary; people cannot communicate and express ideas and feelings with others. This study arises from the necessity to perform a diagnostic that determine if the students of 8 th EGB know and use learning strategies at the moment to learn English vocabulary. Consequently, for this study, it was used descriptive method because it observes and describes the facts without influence them. In the same way, the bibliographical research was applied….